(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Requests for surgical surgery can occur unexpectedly. We can not, in any circumstances when the demand for care arises.Some requests can be queued and scheduled for future dates. These applications are generally surgeries that are not of an urgent nature, they can be delayed without danger to the patient. In medical language, this type of application is generally designated b y the elective surgery, or scheduled.However, a significant proportion of applications within the field of emergency and requires immediate care. This type of application is inherently difficult to predict, and therefore not schedulable and is generally d esignated by the emergency surgery. Depending on the legal structure of the hospital, it may be obliged to accept all emergency patients In this paper, we study the problem of reactive scheduling surgeries in operating rooms with consideration arriving urgent cases.In this context, we propose a reactive programming model procedure whose purpose is to minimize the cost of inserting these urgent cases and also take in consideration the availability of o perating theaters and Surgeons. To solve this problem, we propose a heuristic based on constraint programming